A pilot feasibility study of daily rTMS to modify corticospinal excitability during lower limb immobilization - Raffaella Ricci; Dave Ramsey; Kevin Johnson; Jeffrey J Borckardt; Matthew Vallejo; et al (Dove Medical Press, 2008)
Raffaella Ricci2, Dave Ramsey3, Kevin Johnson1, Jeffrey J Borckardt1, Matthew Vallejo1, Donna R Roberts4, Mark S George11Brain Stimulation Laboratory (BSL), Institute of Psychiatry; 4Department of Radiology, Medical University of South Carolina, Charleston, SC, USA; 2Department of Psychology, University of Turin, Turin, Italy; 3South Carolina Research Authority (SCRA), Columbia, SC, USAAbstract: Short term immobilization of the lower limb is associated with increased corticospinal excitability at 24 hours post cast removal. We wondered whether daily stimulation of the motor cortex might decrease brain reorganization during casting. We tested the feasibility of this approach. Using transcranial magnetic stimulation (TMS), resting motor threshold and recruitment curves were obtained at baseline in 6 healthy participants who then had leg casts placed for 10 days. On 7 of the 10 days subjects received 20 minutes of 1 Hz repetitive TMS (rTMS). TMS measures were then recorded immediately after and 24 hours post cast removal. Four of 6 subjects completed the study. At the group level there were no changes in excitability following cast removal. At the individual level, two participants did not show any change, 1 participant had higher and one lower excitability 24 hours after cast removal. Daily rTMS over motor cortex is feasible during casting and may modify neuroplastic changes occurring during limb disuse. A prospective double blind study is warranted to test whether daily rTMS might improve outcome in subjects undergoing casting, and perhaps in other forms of limb disuse such as those following brain injury or weightlessness in space flight.Keywords: motor cortex, plasticity, rTMS, limb disuse, motor recovery